Testing time-place learning in the cichlid fish Nile tilapia - Delicio, H. C.; Luchiari, A. C.; Barreto, R. E.; Marcondes, A. L. (Springer, 2006)
Time-place learning based on food association was investigated in the fish Nile tilapia. During a 30-day period, food was placed at one side of the aquarium (containing three compartments) in the morning and at the opposite side in the afternoon. Learning was inferred by the number of correct side choices of all fish in each day of test (15th, 30th). During the test day, fish were not fed. The Nile tilapia did not learn to switch sides at the correct day period in order to get food, suggesting thus that this species does not have time-place learning ability.
Keywords: time-place learning; feeding; fish; Nile tilapia; Oreochromis niloticus